TOR and SnRK1 fine tune SPEECHLESS transcription and protein stability to optimize stomatal development in response to exogenously supplied sugar. Issue 1 (8th February 2022) - Han, Chao; Qiao, Yan; Yao, Lianmei; Hao, Wei; Liu, Yue; Shi, Wen; Fan, Min; Bai, Ming‐Yi
Summary: In Arabidopsis, the differentiation of epidermal cells into stomata is regulated by endogenous and environmental signals. Sugar is required for plant epidermal cell proliferation and differentiation. However, it is unclear how epidermal cells maintain division and differentiation to generate proper amounts of stomata in response to different sugar availability. Here, we show that two evolutionarily conserved kinase Snf1‐related protein kinase 1 (SnRK1) and Target of rapamycin (TOR) play critical roles in the regulation of stomatal development under different sugar availability. When plants are grown on a medium containing 1% sucrose, sucrose‐activated TOR promotes the stomatal development by inducing the expression of SPEECHLESS (SPCH), a master regulator of stomatal development. SnRK1 promotes stomatal development through phosphorylating and stabilizing SPCH. However, under the high sucrose conditions, the highly accumulated trehalose‐6‐phosphate (Tre6P) represses the activity of KIN10, the catalytic α‐subunit of SnRK1, by reducing the interaction between KIN10 and its upstream kinase, consequently promoting SPCH degradation and inhibiting stomatal development. Our findings revealed that TOR and SnRK1 finely regulate SPCH expression and protein stability to optimize the stomatal development in response to exogenously supplied sugar.